URGENSI KEPALA MADRASAH DALAM MENGELOLA SUMBER DAYA MANUSIA - Yaqien, Nurul (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2011)
The development of Islamic education, especially in Madrasah is needed to improve the quality of religious education. Madrasah is the representation of implementation the Islamic kaffah, because Madrasah is believed to be able to integrate the religion and modern knowledge to the students. The best education will produce the best students too. This is reflective of the activities what the students do in the process of education program. The succed of Madrasah principal in managing his educational institution is a key of success to increase the quality of madrasah especially to develop of human resources.Key words: Head Master, Management, Human resources